2017
DOI: 10.1038/s41598-017-06661-7
|View full text |Cite
|
Sign up to set email alerts
|

Skin renewal activity of non-thermal plasma through the activation of β-catenin in keratinocytes

Abstract: For recent years, devices that generate non-thermal plasma (NTP) have been introduced into the field of dermatology. Since NTP has demonstrated strong anti-pathogenic activity with safety of use, NTP was first applied to sterilize the skin surface to aid in the healing of various kinds of skin diseases. However, the effect of NTP on skin regeneration has not yet been fully explored. In this study, the effect of NTP on the growth of keratinocytes was tested using the HaCaT human keratinocyte cell line and HRM2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 38 publications
3
47
0
Order By: Relevance
“…These clinical experiences confirm a very early hypothesis in plasma medicine research, that plasma effects on wound healing may be a result of a two-step activity: antiseptics on wound surface in combination with stimulation of tissue regeneration (67) in several in vivo animal experiments (69,(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90) and in human volunteers or patients with reasonably defined wounds (91)(92)(93). It has to be pointed out that these lastmentioned wound healing effects in vivo were demonstrated in acute wounds without any interfering microbial contamination.…”
Section: Biological Plasma Effects and Its Medical Use: Focus On Wounsupporting
confidence: 68%
“…These clinical experiences confirm a very early hypothesis in plasma medicine research, that plasma effects on wound healing may be a result of a two-step activity: antiseptics on wound surface in combination with stimulation of tissue regeneration (67) in several in vivo animal experiments (69,(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90) and in human volunteers or patients with reasonably defined wounds (91)(92)(93). It has to be pointed out that these lastmentioned wound healing effects in vivo were demonstrated in acute wounds without any interfering microbial contamination.…”
Section: Biological Plasma Effects and Its Medical Use: Focus On Wounsupporting
confidence: 68%
“…A similar result was observed by the methanol fraction of the extract of Centella asiatica (100 μg/ml) that increased the cell migration rate, besides assisting in the remodeling during cicatrization of excisional wounds in rabbits (Azis et al, 2017). Epidermal cell turnover is fundamental for rapid wound healing, in which keratinocytes are stimulated to proliferate by regulating growth factors and intercellular contact (J. H. Choi et al, 2017).…”
Section: Discussionsupporting
confidence: 54%
“…They are also essential for a better and fast healing of wounds caused from injuries, ulcers or tumor removal (123,124). A study has demonstrated that NTP can be employed in skin regenerating (125). It was shown that NTP allows keratinocytes to escape from G1 cell cycle arrest, increases the cell proportion in S and G2 phases, causes translocation of beta-catenin to nucleus and induces the transcription of target genes without damaging DNA (125).…”
Section: Roles Of Ntp In Skin Decontamination Skin Renewal and Skin mentioning
confidence: 99%
“…A study has demonstrated that NTP can be employed in skin regenerating (125). It was shown that NTP allows keratinocytes to escape from G1 cell cycle arrest, increases the cell proportion in S and G2 phases, causes translocation of beta-catenin to nucleus and induces the transcription of target genes without damaging DNA (125). Moreover, another study has tested the effects of cold argon plasma on eggs of blow fly (126).…”
Section: Roles Of Ntp In Skin Decontamination Skin Renewal and Skin mentioning
confidence: 99%